In search of a safe place : abused women and culturally sensitive services - Agnew, Vijay, 1946- (University of Toronto Press, 1998)
"Marginalized in the larger society and in the mainstream women's movement, immigrant women are also outsiders in women's shelters, where racially sensitive and linguistically appropriate counselling is generally unavailable. In this book, Vijay Agnew documents the struggles of Canadian women's centres to provide better services to victims of wife abuse from Asia, Africa, and the Caribbean."--Jacket